Recommendations of the International Society of Intraoperative Neurophysiology for intraoperative somatosensory evoked potentials. Issue 1 (January 2019) - MacDonald, D.B.; Dong, C.; Quatrale, R.; Sala, F.; Skinner, S.; Soto, F.; Szelényi, A.
Highlights: This article reviews and forms recommendations for intraoperative SEPs. It endorses SEP optimization to enhance surgical feedback speed and accuracy. It supports an adaptive warning criterion to adjust for baseline drift and variability. Abstract: Intraoperative somatosensory evoked potentials (SEPs) provide dorsal somatosensory system functional and localizing information, and complement motor evoked potentials. Correct application and interpretation require in-depth knowledge of relevant anatomy, electrophysiology, and techniques. It is advisable to facilitate cortical SEPs with total intravenous propofol–opioid or similarly favorable anesthesia. Moreover, SEP optimization is recommended to enhance surgical feedback speed and accuracy by maximizing signal-to-noise ratio (SNR); it consists of selecting highest-SNR peripheral and cortical derivations while omitting low-SNR channels. Confounding factors causing non-surgical SEP reduction should be excluded before issuing a warning. It is advisable to facilitate their identification with peripheral SEP controls and cortical SEP systemic controls whenever possible. Warning criteria should adjust for baseline drift and reproducibility. The recommended adaptive warning criterion is visually obvious amplitude reduction from recent pre-change values and clearly exceeding trial-to-trial variability, particularly when abrupt and focal. Acquisition and interpretation should be done by qualified technical and professional level personnel. Indications for SEP monitoring include intracranial, posterior fossa, and spinal neurosurgery, as well as orthopedic spine, cerebrovascular, and descending aortic surgery. Indications for SEP mapping include sensorimotor cortex and dorsal column midline identification. Future advances could modify current recommendations.